THE GOVERNMENT’S ROLE IN FACING THE INJUSTICE OF GLOBAL TRADE - Muhammad Sood (Fakultas Hukum Universitas Mataram, 2013)
Despite the controversy about the liberalization of trade, however the government of Indonesia has ratified the WTO provisions by the discharge of the Act Number 7 Year 1994 concerning the Agreement on establishment of the World Trade Organization. This is a fact of law that formed base on the political will of the Indonesian government to encourage the free trade system as an impact of the circulation of the vital flow of goods, services, capital and labor among countries in both the regional and global level. This change mainly supported by the development of science and technology is growing rapidly and broadly, therefore nations must work together in both the global and regional level. The benefits have been felt by Indonesia in the presence of trade between nations is successful in developing its exports, especially non-oil exports. Therefore, in international trade requires a system of international trade organization to promote the establishment of a free market, fair and open to all countries. In the world trading system, the Government of Indonesia has been struggling along with other countries actively participated success of multilateral trade negotiations within the framework of the GATT Uruguay Round in 1994, the main objective is not only focused on free trade but also fair trade. For the agenda, the Indonesian government has taken some steps of deregulation and de-bureaucratization to improve efficiency of the national economy. The program will continue to be struggled as a strategic step and is the increase of non-oil exports in order to achieve the goals of economic development in Indonesia.Keywords: Government role, trade globalization, international trade